2010
DOI: 10.1098/rspb.2010.1738
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance affects short-term facilitation, but not long-term saturation, of exotic plant invasion in New Zealand forest

Abstract: We investigate the spread of an exotic herb, Hieracium lepidulum, into a New Zealand Nothofagus forest with the aim of understanding how stand-development of tree populations, propagule pressure and invader persistence, affect invasion across the landscape and within communities. Using data repeatedly collected over 35 years, from 250 locations, we parametrize continuous-time Markov chain models and use these models to examine future projections of the invasion under a range of hypothetical scenarios. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…While the intact forest interior appears relatively resistant to invasion by H. lepidulum, spread through forested areas is likely facilitated by the presence of open creeks and treefall gaps, which are much less invasion resistant. Spence et al (2011b) similarly found that the probability of H. lepidulum invasion in New Zealand mountain beech forest was high following canopy disturbance. Projected levels of H. lepidulum in intact forest were driven by persistence of individuals already established, and from propagule supply from creek margins and forest edges (Spence et al 2011b).…”
Section: Species Distribution-invasion Resistance Mismatchmentioning
confidence: 87%
See 1 more Smart Citation
“…While the intact forest interior appears relatively resistant to invasion by H. lepidulum, spread through forested areas is likely facilitated by the presence of open creeks and treefall gaps, which are much less invasion resistant. Spence et al (2011b) similarly found that the probability of H. lepidulum invasion in New Zealand mountain beech forest was high following canopy disturbance. Projected levels of H. lepidulum in intact forest were driven by persistence of individuals already established, and from propagule supply from creek margins and forest edges (Spence et al 2011b).…”
Section: Species Distribution-invasion Resistance Mismatchmentioning
confidence: 87%
“…Spence et al (2011b) similarly found that the probability of H. lepidulum invasion in New Zealand mountain beech forest was high following canopy disturbance. Projected levels of H. lepidulum in intact forest were driven by persistence of individuals already established, and from propagule supply from creek margins and forest edges (Spence et al 2011b). The clear implication is that the density of H. lepidulum is likely to increase in subalpine habitats as the population continues to expand and the rate at which propagules reach sites above treeline increases.…”
Section: Species Distribution-invasion Resistance Mismatchmentioning
confidence: 87%
“…Because we were specifically interested in the degree to which mortality was contagious, that is, occurring near sites of previous mortality, we developed an index that categorized the local neighborhood, for each focal tree, as either 'disturbed' or 'undisturbed'. The index was based on those developed by Coomes and Allen (2007) and Spence et al (2011) and categorized neighborhoods into developmental stages based on previous trends in basal area, stem density and mean stem diameter (i.e., in our case over the 1986-2001 period). Stands with declining basal area, stem density and mean stem diameter were classified as 'disturbed', distinguishing them from undisturbed stands (e.g., regenerating and thinning stands which typically did not meet all of these criteria; Coomes and Allen, 2007;Spence et al, 2011).…”
Section: Individual-based Mortality Modelsmentioning
confidence: 99%
“…The index was based on those developed by Coomes and Allen (2007) and Spence et al (2011) and categorized neighborhoods into developmental stages based on previous trends in basal area, stem density and mean stem diameter (i.e., in our case over the 1986-2001 period). Stands with declining basal area, stem density and mean stem diameter were classified as 'disturbed', distinguishing them from undisturbed stands (e.g., regenerating and thinning stands which typically did not meet all of these criteria; Coomes and Allen, 2007;Spence et al, 2011). Comparison of mortality rates of trees with neighborhoods classified as 'disturbed', or not, allowed us to address Hypothesis 2.…”
Section: Individual-based Mortality Modelsmentioning
confidence: 99%
“…Although the degree of invasion into forest interiors was still low, ruderal and road sites in Nonguén can act as a source for alien species in particular after natural or anthropogenic canopy openings (Spence et al 2011). Although there is not yet an official management plan for the Nonguén reserve, a substitution of alien-dominated plantations by native species is planned (CONAF personal communication).…”
Section: Discussionmentioning
confidence: 98%